2005
DOI: 10.1074/jbc.m410436200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism of Interaction of p85 Subunit of Phosphatidylinositol 3-Kinase and ErbB3 Receptor-derived Phosphotyrosyl Peptides

Abstract: Ligand-activated and tyrosine-phosphorylated ErbB3 receptor binds to the SH2 domain of the p85 subunit of phosphatidylinositol 3-kinase and initiates intracellular signaling. Here, we studied the interactions between the N-(N-SH2) and C-(C-SH2) terminal SH2 domains of the p85 subunit of the phosphatidylinositol 3-kinase and eight ErbB3 receptor-derived phosphotyrosyl peptides (P-peptides) by using molecular dynamics, free energy, and surface plasmon resonance (SPR) analyses. In SPR analysis, these P-peptides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…These data further suggests that phosphorylation of the tyrosine motif plays an important role in trafficking of CD1d. Indeed, the phospho-tyrosine motif, pYXXM present in insulin receptor substrate-1, plateletderived growth factor receptor, and ErbB2, 3 receptors binds with the SH2 domain of the p85 subunit of PI 3-kinase (52)(53)(54)(55)(56)(57)(58). Additional studies in AP-3Ϫ/Ϫmice are needed to further clarify specific interaction of PI 3-kinase on trafficking of CD1d protein.…”
Section: Discussionmentioning
confidence: 99%
“…These data further suggests that phosphorylation of the tyrosine motif plays an important role in trafficking of CD1d. Indeed, the phospho-tyrosine motif, pYXXM present in insulin receptor substrate-1, plateletderived growth factor receptor, and ErbB2, 3 receptors binds with the SH2 domain of the p85 subunit of PI 3-kinase (52)(53)(54)(55)(56)(57)(58). Additional studies in AP-3Ϫ/Ϫmice are needed to further clarify specific interaction of PI 3-kinase on trafficking of CD1d protein.…”
Section: Discussionmentioning
confidence: 99%
“…136 These interactions involve the N-terminal SH2 domain of p85, with the two phosphotyrosine-binding sites in this domain each interacting preferentially with certain phosphotyrosyl peptides from ERBB3. 137 For the three pairs of tyrosine residues separated by a glutamic acid, the first Tyr in each case binds p85. 132 Doubly phosphorylated tripeptides also bound p85, with the two phosphotyrosine-binding sites in p85 possibly each engaging a different but nearby phosphotyrosine.…”
Section: Proteins Binding With Phosphotyrosines In Erbb3′s Cytoplasmimentioning
confidence: 99%
“…132 Doubly phosphorylated tripeptides also bound p85, with the two phosphotyrosine-binding sites in p85 possibly each engaging a different but nearby phosphotyrosine. 137 Because of the high number of binding sites, ERBB3 is viewed as a possible scaffold protein for PI3KR.…”
Section: Proteins Binding With Phosphotyrosines In Erbb3′s Cytoplasmimentioning
confidence: 99%
“…Component analysis of the calculated binding free energies reveled that van der Waals interaction between the Grb2 and the phosphotyrosyl peptide was the dominant factor for specificity and binding affinity. Recently, they successfully conducted MD simulations followed by MM-PBSA free energy calculations to identify the binding mode of eight ErbB3 receptor-derived phosphotyrosyl peptides in complex with the SH2 domain of the p85 subunit of phosphatidylinositol 3-kinase [79]. They found that some peptides favored the N1 binding site in the N-terminal region, while the others favored the N2 binding site in the C-terminal region as indicated by the MM-PBSA binding free energies at both sites.…”
Section: Protein-protein Protein-peptide Interactionsmentioning
confidence: 99%